2017 IEEE 30th Canadian Conference on Electrical and Computer Engineering (CCECE) 2017
DOI: 10.1109/ccece.2017.7946732
|View full text |Cite
|
Sign up to set email alerts
|

Low complexity H.264 list decoder for enhanced quality real-time video over IP

Abstract: This paper presents a novel list decoding approach exploiting the receiver side user datagram protocol (UDP) checksum. The proposed method identifies the possible locations of errors in the packet by analyzing the calculated UDP checksum value at the receiver side. This makes it possible to considerably reduce the number of candidate bitstreams in comparison to conventional list decoding approaches. When a packet composed of N bits contains a single bit in error, instead of considering N candidate bitstreams, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In order to further increase the proposed method's error correction performance, it can be jointly used with other methods providing a list of potential error patterns as their output. For example, the work on UDP checksum proposed in [9], [26], [27] can be combined with our algorithm. Crosschecking both candidate lists would generate a matching list with a reduced number of entries.…”
Section: E Future Workmentioning
confidence: 99%
“…In order to further increase the proposed method's error correction performance, it can be jointly used with other methods providing a list of potential error patterns as their output. For example, the work on UDP checksum proposed in [9], [26], [27] can be combined with our algorithm. Crosschecking both candidate lists would generate a matching list with a reduced number of entries.…”
Section: E Future Workmentioning
confidence: 99%
“…One of the most important video coding standards, video coding standard called H.264/AVC. This standard remarkably has better coding efficiency than its predecessors, and has attracted considerable interest from the academic and developer communities [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…a fixed or floating point log-likelihood ratio (LLR) value for each bit of the packet, throughout the protocol stack (from the physical up to the application layer), is complex to implement and deploy in practice. In our previous work [29], we studied the checksum bit pattern for the case of a single-bit error, and showed that it could be exploited to eliminate 97% of the candidate bitstreams considered by list decoding approaches. The proposed method was tested on H.264 CAVLC coded sequences.…”
Section: Introductionmentioning
confidence: 99%